2019
DOI: 10.3390/microorganisms7120698
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mechanisms Lowering Susceptibility to Flumequine among Bacteria Isolated from Chilean Salmonid Farms

Abstract: Despite their great importance for human therapy, quinolones are still used in Chilean salmon farming, with flumequine and oxolinic acid currently approved for use in this industry. The aim of this study was to improve our knowledge of the mechanisms conferring low susceptibility or resistance to quinolones among bacteria recovered from Chilean salmon farms. Sixty-five isolates exhibiting resistance, reduced susceptibility, or susceptibility to flumequine recovered from salmon farms were identified by their 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…It has been observed that bacteria carrying mutations in the quinolone action target enzymes can exhibit higher MIC values when efflux systems are expressed [ 18 , 282 , 290 ]. The same result was observed in Pseudomonas isolated from freshwater environments associated with fish farming [ 283 ]. Furthermore, it has been reported that enteric bacteria with high and intermediate resistance to quinolones exhibited the co-occurrence of qnr genes and mutations in the GyrA and ParC subunits [ 122 ].…”
Section: Quinolone Resistance Genes ( Qnr )supporting
confidence: 79%
See 1 more Smart Citation
“…It has been observed that bacteria carrying mutations in the quinolone action target enzymes can exhibit higher MIC values when efflux systems are expressed [ 18 , 282 , 290 ]. The same result was observed in Pseudomonas isolated from freshwater environments associated with fish farming [ 283 ]. Furthermore, it has been reported that enteric bacteria with high and intermediate resistance to quinolones exhibited the co-occurrence of qnr genes and mutations in the GyrA and ParC subunits [ 122 ].…”
Section: Quinolone Resistance Genes ( Qnr )supporting
confidence: 79%
“…The overexpression of various efflux pumps can lead to low-level resistance [ 277 , 278 , 279 ], lowering the cytoplasmic concentration of antimicrobials inside the cell and generating an advantage for the evolutionary selection of high-resistance strains [ 279 , 280 , 281 ]. In support of this trend, the combined activity of qnr genes with multidrug efflux systems drastically reducing the susceptibility to quinolones and providing a high-level of quinolone resistance has been reported [ 122 , 282 , 283 ], confirming the additive inhibitory activity of both antimicrobial mechanisms [ 18 ], as postulated in Figure 2 .…”
Section: Quinolone Resistance Genes ( Qnr )supporting
confidence: 55%
“…The hypothesis of bacterial resistance is ruled out because the development of FLUM resistance usually needs much longer time of exposure (more than 150 days). 59,60 Thus, we suggest that the degradation of FLUM in the broth and/or its metabolization within bacterial cell are the principle causes of its low antibacterial activity as reported. 60,61 The treatment with FLUM@TiNTs induced a progressive damage and cells death indicating that TiNTs enhances the drug efficacy thanks to their protection mechanism from degradation and progressive release during the experiment period.…”
Section: Discussionmentioning
confidence: 57%
“… 59,60 Thus, we suggest that the degradation of FLUM in the broth and/or its metabolization within bacterial cell are the principle causes of its low antibacterial activity as reported. 60,61 The treatment with FLUM@TiNTs induced a progressive damage and cells death indicating that TiNTs enhances the drug efficacy thanks to their protection mechanism from degradation and progressive release during the experiment period. Given the advantages of drug encapsulation which include (i) a sustained release that can reduce frequent doses administration and side effects, (ii) an enhanced absorption, 62 the use of TiNTs as FLUM nanocarrier appears as an attractive alternative for better FLUM release and antibacterial efficiency.…”
Section: Discussionmentioning
confidence: 95%
“…The MICs of oxytetracycline of FP105 and FP211-J200 isolates were determined by a microdilution procedure, as recommended by the CLSI guideline M07-A10 [ 60 ] and previously described [ 61 ]. Conical bottom microplates added with a cation-adjusted Mueller–Hinton broth (Difco Labs, NJ, USA) were inoculated with the antibiotic to obtain final series of two-fold concentrations in the range of 0.0625–512 µg/mL, and bacterial suspensions were inoculated in triplicate microplates, delivering approximately 10 4 colony-forming units per well and incubated at 28 °C for 24 h. The reference strains E. coli ATCC 25,922 and Aeromonas salmonicida ATCC 33,658 were included as quality controls, as was recommended [ 21 ].…”
Section: Methodsmentioning
confidence: 99%